Performance Improvement Through Servant Leadership Organizational Support and Communication on Employee Performance: Peningkatan Kinerja Melalui Servant Leadership Dukungan Organisasi dan Komunikasi Terhadap Kinerja Karyawan - Apriyanti, Efa; Abadiyah, Rifdah (Indonesian Journal of Innovation Studies, 2022)
The purpose of this study was to determine the effect of servant leadership, organizational support and communication on employee performance at PT Harapan Sejahtera Karya Utama Sidoarjo. The approach used in this research is a quantitative approach. The population in this study were 200 employees. The sampling technique used is a simple random sampling technique used for this research is purposive sampling. The sample in this study were 133 respondents. Analysis using SPSS software. The results obtained from the influence of servant leadership, organizational support and communication have a significant effect on employee performance. Servant leadership has a significant effect on employee performance, organizational support has a significant effect on employee performance and communication has a significant effect on employee performance.